2009
DOI: 10.1002/art.24250
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the notch pathway in the regulation of matrix metalloproteinase 13 and the dedifferentiation of articular chondrocytes in murine cartilage

Abstract: Objective. To demonstrate the activation of the Notch signaling pathway during changes in the phenotype of chondrocytes in vitro, and to assess the influence of Notch on the production of chondrocyte markers.Methods. Serial monolayer primary cultures of murine articular chondrocytes (MACs), as a model of chondrocyte dedifferentiation, were prepared. MACs were cultured with or without a Notch inhibitor and transfected with different Notch-expressing vectors. The Notch pathway and chondrocyte marker profiles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 93 publications
0
25
0
1
Order By: Relevance
“…Notably, one of the studies showed a cooperation of Notch and transforming growth factor ␤ (TGF-␤) signaling pathways in the process (39). As both MMP-1 and MMP-13 expression levels are known to be regulated by TGF-␤-induced signals (40) and Notch signaling has been shown to affect MMP-13 expression (41,42), it is possible that SLFN5 controls MMP-1 and MMP-13 expression, as well as cell motility and invasion through its effects on NOTCH/TGF-␤ signaling. Expression of MMPs can also be modulated by additional pathways (43).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, one of the studies showed a cooperation of Notch and transforming growth factor ␤ (TGF-␤) signaling pathways in the process (39). As both MMP-1 and MMP-13 expression levels are known to be regulated by TGF-␤-induced signals (40) and Notch signaling has been shown to affect MMP-13 expression (41,42), it is possible that SLFN5 controls MMP-1 and MMP-13 expression, as well as cell motility and invasion through its effects on NOTCH/TGF-␤ signaling. Expression of MMPs can also be modulated by additional pathways (43).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous observations that showed increased NOTCH signaling in stem cells and other cell types in response to cytokines (24 -27). In osteoarthritic cartilage, a condition linked to production of proinflammatory cytokines, the role of NOTCH1, JAGGED1, and HES5 has been associated to the expression of a reparative phenotype (28), although increase in NOTCH signaling promotes dedifferentiated phenotype of articular chondrocytes (29). Likewise, in the NP, the activity of this signaling system, in the presence of TNF-␣ and IL-1␤ possibly indicates an attempt by the cells to promote tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription was performed on 1 g of total RNA, using the Omniscript RT kit (Qiagen). Messenger RNA (mRNA) for IR was quantified using the LightCycler LC480 (Roche Diagnostics) as described (25). Specific primers for complementary DNA (cDNA) were chosen with the LightCycler Probe Design 2 program.…”
Section: Methodsmentioning
confidence: 99%